Four new species of Macrostomus Wiedemann and a checklist of Empididae s. str. (Diptera) from Peru - Rafael, José Albertino; Marques, Dayse Willkenia A. (Zootaxa, 2021)
Twelve Peruvian species of Macrostomus Wiedemann were studied. Macrostomus apicalis (Bezzi, 1909) is redescribed based on female holotype. Four new species are described: M. chelicercus sp. nov. (type-locality: Cuzco, Quincemil), M. contortus sp. nov. (type-locality: Cuzco, Quincemil), M. hyalopteryx sp. nov. (type-locality: Cuzco, Ttio) and M. unilineatus sp. nov. (type-locality: Junin, Oxapampa). A key to the 12 species of Macrostomus found in Peru is presented. A checklist of 50 known species of Peruvian Empididae s. str. is included. Atrichopleura schnusei Bezzi, 1909 is excluded from the Peruvian fauna.